Pemberdayaan UMKM Desa Semat melalui Pembinaan Pencatatan Keuangan Usaha Berbasis SAK EMKM untuk Desa Wisata - Sari Rahmadhani; Hasan Abdul Rozak; Taswan Taswan; Sugiharti Sugiharti; Emi Wardati; Ayu Maisyaroh; Ahmad Rofiqi (Penerbit Goodwood, 2026)
Purpose: This community service program aimed to improve financial literacy and bookkeeping skills among MSMEs in Semat Village, Jepara, supporting sustainable business decisions and promoting local tourism based on regional products. Methodology: The program targeted 30 MSMEs, providing two days of training on SAK EMKM templates and Excel-based bookkeeping. Participants then received one month of intensive mentoring focused on daily transaction recording and separating business and personal finances. Evaluation was conducted through pre- and post-tests. Results: Participants showed significant improvement in both hard and soft skills. Financial recording skills rose from 20% to 88% (+68%), and the ability to separate business and personal finances increased from 12% to 84% (+72%). All participants demonstrated the ability to identify positive cash flow and prepare independent financial reports. Conclusions: The mentoring program successfully enhanced financial literacy, laying a foundation for sustainable business practices and long-term growth in Kembang Turi based village tourism. Limitations: The study is limited by the short mentoring period (one month) and small sample size, which restricts long-term impact measurement. Additionally, no control group was used. Contributions: The study provides a practical financial management model for rural tourism-based MSMEs, offering insights for academics, policy recommendations for local governments, and templates for practitioners.